Robust Standard Error Panel Regression of Firm Size, Leverage, Profitability on Firm Value: Indonesian Mining 2022–2024 - Muh Qodri Alfairus; Muhammad Raihan Mubaraq; Alia Rezki Amalia (Program Studi Statistika Fakultas MIPA UNM, 2026)
Corporate financial information such as firm size, leverage, and profitability sends signals to the market that are reflected in firm value. However, previous studies have yielded inconsistent results, likely due to differences in estimation methods and the disregard of violations of classical assumptions in panel data. This study aims to analyze the effects of firm size (Size), leverage (DER), and profitability (ROA) on firm value (PBV) by applying panel data regression with robust standard error correction. Data were collected from 21 mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, yielding 63 observations. The model selected based on the Chow Test (p=1.46E-09) and the Hausman Test (p=0.002) is the Fixed Effects Model (FEM). The results of the classical assumption tests indicate violations of heteroscedasticity (p=0.029) and autocorrelation (p=0.005), so the estimation was continued using cluster-robust standard errors (clustering by time). After adjusting for the model, it was found that all three variables simultaneously had a significant effect on firm value (F-statistic, p = 0.0538). Partially, firm size had a significant negative effect (coefficient -0.481; p=0.038), leverage had a significant positive effect (coefficient 0.672; p=0.018), and profitability had a marginally significant negative effect (coefficient -0.796; p=0.092). An R-squared value of 17.6% indicates that there are still other factors outside the model that influence firm value. The conclusion of this study confirms that in the context of the Indonesian mining sector in the post-pandemic period, the market responds negatively to companies with large assets and high profitability, but responds positively to increased debt. These findings imply that investors should not focus solely on short-term profitability, and that company management should determine the optimal capital structure to increase firm value.